2017
DOI: 10.1021/acs.analchem.7b00171
|View full text |Cite
|
Sign up to set email alerts
|

Whole Blood Metabolomics by 1H NMR Spectroscopy Provides a New Opportunity To Evaluate Coenzymes and Antioxidants

Abstract: Conventional human blood metabolomics employs serum or plasma and provides a wealth of metabolic information therein. However, this approach lacks the ability to measure and evaluate important metabolites such as coenzymes and antioxidants that are present at high concentrations in red blood cells. As an important alternative to serum/plasma metabolomics, we show here that a simple 1H NMR experiment can simultaneously measure coenzymes and antioxidants in extracts of whole human blood, in addition to the nearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(87 citation statements)
references
References 41 publications
3
84
0
Order By: Relevance
“…Metabolomics profiling by NMR has been often performed by one-dimensional (1D) 1 H NMR experiments [ 26 ]. The advantage of 1D 1 H NMR is its short acquisition time, which is typically less than an hour/sample and high sensitivity; it is able to detect metabolites down to single digit μM concentration [ 27 ]. When this is coupled to a manual peak fitting or a manual spike-in approach, 1D 1 H NMR is capable to provide absolute concentration of dozens to hundred of metabolites in metabolomics samples [ 28 ].…”
Section: Targeted Metabolomicsmentioning
confidence: 99%
“…Metabolomics profiling by NMR has been often performed by one-dimensional (1D) 1 H NMR experiments [ 26 ]. The advantage of 1D 1 H NMR is its short acquisition time, which is typically less than an hour/sample and high sensitivity; it is able to detect metabolites down to single digit μM concentration [ 27 ]. When this is coupled to a manual peak fitting or a manual spike-in approach, 1D 1 H NMR is capable to provide absolute concentration of dozens to hundred of metabolites in metabolomics samples [ 28 ].…”
Section: Targeted Metabolomicsmentioning
confidence: 99%
“…Among others, important metabolites identified in whole blood extracts were NAD + , NADH, NADP + , NADPH, ATP, ADP, AMP, GSH and GSSG. A comparison of whole blood and plasma NMR spectra revealed that the redox coenzymes, energy coenzymes and antioxidants were detected only in whole blood [ 13 ] ( Figure 8 ).…”
Section: Coenzymes In Human Whole Bloodmentioning
confidence: 99%
“…This new capability is significant in that there was no NMR or MS method that can enable analysis of major coenzymes and antioxidants in whole blood. The new NMR method is anticipated to pave new ways for blood metabolomics [ 13 ].…”
Section: Coenzymes In Human Whole Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein precipitation by methanol, chloroform, or a mixture of organic solvents is an efficient method to remove the proteins from the system. The use of this method with biological samples as has been reported in the literature [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%